Audible stirrings : how Singaporeans are resisting the suppression of Chinese dialects. - Chay, Felda Pei Ying. (2009)
Our project titled: “Audible stirrings: How Singaporeans are resisting the suppression of Chinese dialects”, draws attention to the pockets of society where Singaporeans seek to keep these languages alive despite the local government’s stance to stamp them out. We investigate the policy's implications on Singapore society.